PELAPORAN SURVEILANS DEMAM BERDARAH BERBASIS SMS DI KOTA YOGYAKARTA - Anwar Dwi Cahyono; Tri Baskoro Tunggul Satoto; Lutfan Lazuardi (Departemen Kebijakan dan Manajemen Kesehatan, Fakultas Kedokteran, Kesehatan Masyarakat, dan Keperawatan, Universitas Gadjah Mada, Yogyakarta Jl. Farmako Sekip Utara Yogyakarta 55281 Telp 0274-547490, 2016)
Background: The need of accurate and accelerate informationlead to decision making in order to dengue treatment now adays is high in Yogyakarta City Government. This was related tothe fact that there is a delay more than 24 hours from patient isdiagnosed with dengue until the case was reported fromhospital. Objective: to describe dengue surveillance report using SMSgateway. Methods: This research is using qualitative approach.Respondent from this research are Head of Disease ControlDepartment, Head of Health Promotion and Health InformationSystem and the others are hospital staffs who is responsible fordengue reporting. Result: SMS based reporting does not show the real amountnumber of dengue cases for a year, during the implementationthere has been 187 cases from the SMS. This was far beyondthe real number of cases which is 411 cases. Conclusion: This SMS based for dengue surveillance reportingcannot be the information that can lead to decision making.